From Romania to the Eastern front: journalists Juan Manuel de la Aldea and Trinidad Nieto Funcia - Moreno Cantano, Antonio César (Historia y Comunicación Social, 2018)
Throughout the decade of the forties proliferated in francoist Spain chronicles and books who fought against communism on Russian soil. One of the clearest examples was the appearance of the work Rumanía. De la Guardia de Hierro a la Guardia Roja, whose authorship corresponded to Hernán-Bastida, pseudonym under which journalists Juan Manuel de la Aldea and Trinidad Nieto Funcia werw hiding. They stationed during World War II in Bucharest, played an important propaganda task strengthening relations between the regime of Antonescu and Franco. To this must be added important activities in the field of espionage for the Axis. In this article we will discuss all these issues as well as major items produced fruit of that experience, both in Spanish and Romanian media. We will draw on various documentary sources (AGA and AMAE), bibliographic and periodicals of interest and little known.